Managerial Ownership Structure, Presence of Female Directors and Independent Commissioners on Organizational Performance - Sri Maryati; Asfeni Nurullah; Hendra Prasetyo (Universitas KH. Abdul Chalim Mojokerto, 2024)
Organizational performance cannot be separated from the role of management that manages and filters every activity of the organization. This study aims to empirically test the relationship between Managerial Ownership Structure, the Existence of Female Directors and Independent Commissioners on Organizational Performance. By using the upper echelon theory that connects organizational strategy and the role of management involved. The data used are secondary data, manufacturing companies in 2021-2023 listed on idx.co.id. The data was processed using Warp-PLs assistance. Based on the results of the analysis, it was concluded that the existence of an independent board of commissioners and ownership concentration did not affect organizational performance, while the presence of female directors did affect organizational performance. Considering the role of women as directors in an organization is one way to improve organizational performance.